2012
DOI: 10.2217/nnm.12.105
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Alzheimer‘S and Parkinson‘S Disease From Exhaled Breath Using Nanomaterial-Based Sensors

Abstract: The breath prints that were identified with combinations of nanomaterial-based sensors have future potential as cost-effective, fast and reliable biomarkers for AD and PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
145
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 179 publications
(147 citation statements)
references
References 47 publications
1
145
0
1
Order By: Relevance
“…8,10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] As the sensors array approach provides results in a "black-box" approach (based on trained sensors and an algorithm), we use also gas chromatography linked with mass spectrometry to gain information about the chemical and composition nature of the examined samples.…”
mentioning
confidence: 99%
“…8,10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] As the sensors array approach provides results in a "black-box" approach (based on trained sensors and an algorithm), we use also gas chromatography linked with mass spectrometry to gain information about the chemical and composition nature of the examined samples.…”
mentioning
confidence: 99%
“…A number of volatile organic compounds like styrene, butylated hydroxytoluene and hexadecane have been found in the breath of PD patients [65]. As an example of the use of nanotechnology in the sensing of such novel compounds, organically functionalized nanoparticles like carbon nanotubes and gold nanoparticles were used by Tisch and co-workers [66]. The sensors were effective in distinguishing the breath prints of PD from healthy states with an accuracy of 78 % [66].…”
Section: Other Novel Conceptsmentioning
confidence: 99%
“…As an example of the use of nanotechnology in the sensing of such novel compounds, organically functionalized nanoparticles like carbon nanotubes and gold nanoparticles were used by Tisch and co-workers [66]. The sensors were effective in distinguishing the breath prints of PD from healthy states with an accuracy of 78 % [66]. Similarly, the technology could identify Alzheimer's disease and differentiate it from PD.…”
Section: Other Novel Conceptsmentioning
confidence: 99%
“…[1][2][3][4][5] These arrays could meet the growing demand for rapid and flexible online detection of a wide range of chemical and biological agents in different branches of industry, homeland security, 5,6 environmental monitoring, 5,7,8 and medical diagnostics [1][2][3][4][5][9][10][11][12][13][14][15][16][17][18][19][20] . Combined with statistical algorithms, these sensor arrays can provide convenient bionics of the mammalian olfactory system for identifying complex gas samples, without the necessity of identifying their separate ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Sensors with electronic and electro-acoustic transduction mechanisms, such as chemically sensitive resistors [24][25][26][27][28][29][30][31][32][33] and quartz-crystal microbalance (QCM) sensors [34][35][36] are among the most attractive and widespread elements for sensing applications that involve the detection and classification of volatile organic compounds (VOCs) in the gas phase. 9,11,13,16,19,20,24,37 Recently, we have shown that polycyclic aromatic hydrocarbon (PAH) derivatives as sensing materials in chemiresistors, field effect transistors or QCM sensors can provide good sensitivity and robust selectivity towards different polar and nonpolar VOCs, while being highly tolerant even to drastic humidity variations. 11,33,34,[38][39][40] For example, we have shown that a bilayer structure with a quasi 2D network of single wall carbon nanotubes (RNSWCNTs) as an under-layer and a micron-thick PAH film as an overcoat, can provide excellent detection and classification between polar and nonpolar VOCs, both in dry atmospheres with ~ 5% relative humidity (RH) and in almost fully humidified atmospheres (~80% RH).…”
Section: Introductionmentioning
confidence: 99%